Lipid profile and its correlation with C-reactive protein in patients of acute myocardial infarction - Rathore, Vedika; Singh, Neelima; Rastogi, Puneet; Mahat, Roshan Kumar; Mishra, Mritunjay Kumar; Shrivastava, Reetika (International Journal of Research in Medical Sciences, 2017)
Background: Acute myocardial infarction (AMI) is a significant cause of morbidity and mortality worldwide, which results from occlusion of coronary artery. Dyslipidemia is a major risk factor of AMI. C-reactive protein (CRP) is an acute phase protein, synthesized by hepatocytes in response to cytokines released into circulation by activated leukocytes and has been found to increase after AMI. The objective of the present study is to investigate lipid profile in AMI patients and correlate it with inflammatory marker i.e. CRP. Methods: The present study includes 150 AMI patients and 100 normal healthy individuals as controls. In all the cases and controls, serum lipid profile and inflammatory marker were measured by diagnostic kits supplied by ERBA. Results: The levels of lipid profile and inflammatory marker were significantly altered in the AMI cases compared to controls. We found significantly higher levels of total cholesterol, TG, LDL, VLDL, CRP and lower level of HDL in AMI compared to that of control subjects. We also found strong positive correlation of CRP with total cholesterol, triglyceride, LDL-C and VLDL-C and significant negative correlation with HDL-C in AMI patients. Conclusions: We found alterations in the lipid profile and inflammatory marker in AMI cases; hence, all the people should undergo regular check up including lipid profile evaluation and inflammatory marker such as CRP to decrease the incidence, morbidity and mortality from the disease.